Fabrication and Photoresponse of Novel Carboxymethylcellulose (CMC) Based Bacteriorhodopsin (bR) Sensor - Vengadesh, P.; Majid, W.H.A.; Shanmugam, S.A.; Low, K.S. (2006)
A single-pixel dry-type reconstituted bacteriorhodopsin (bR) sensor (Au/CMC + bR/ITO) incorporating carboxyrnethylcellulose (CMC) as the artificial membrane is fabricated according to a protocol developed to investigate signal acquisition from the proposed biosensor. Droplets of reconstituted purple membrane (PM) containing bR applied onto a gel-like solution of CMC placed on gold electrodes (anode) are allowed to dry under an electric field, utilising the PM fragment's net negative charge and electric dipole moment. The resulting bR matrix thin film with high molecular orientation is finally sandwiched together with a semi-transparent indium titanium oxide (ITO) counter electrode and proper electrical connections made to form a single pixel bR-CMC photosensor. Efficient and reproducible photoresponse observed upon illumination clearly exhibits the potential of the proposed biosensor for future photosensing works. (C) 2006 Elsevier B.V. All rights reserved.